Overview of the first 1000 days of life and stunting in toddlers 0-2 years old in Tegallalang District, Bali Province - Pradnyawati, Luh Gede; Dewa Ayu Putu Ratna Juwita; Komang Triyani Kartinawati; Made Indra Wijaya; Anak Agung Sagung Mirah Prabandari (Journal of International Surgery and Clinical Medicine, 2023)
Introduction: The most crucial time for a child's physical and cognitive development is the first 1000 days of life. Their nutritional state will influence toddlers' future health, intelligence, and productivity in the first 1000 days of life. The study aimed to describe the first 1000 days of life in toddlers aged 0-2 years. Methods: This cross-sectional study used a household survey in 30 clusters. Five samples of children between 0-1 years old and five samples between the ages of 1-2 years old were selected by simple random sampling from each census block for 300 respondents. Nutrition adequacy was analyzed in Nutrisurvey 2007 program. All data were analyzed descriptively in the SPSS program. Results: The prevalence of stunting in children aged 0-2 in Tegallalang District was 12%. Among children 0-1 years old was 8%, while in children aged 1-2 years was 17%. 41% of pregnant women and toddlers were exposed to secondhand smoke. The rate of exclusive breastfeeding was 44%, vitamin A supplementation was 43.7%, deworming treatment was 52%, and only 20% of people had clean water. There were 115 toddlers aged 1-2 years w    deficits in carbohydrates, 140 toddlers with deficits deficiencies, and 80 toddlers with deficits in iron. Conclusion: The problem of stunting in Tegallalang District still exists. Community health workers should encourage women and their male partners regarding second-hand smoke, exclusive breastfeeding, vitamin A supplementation, and deworming treatment. Access to clean water is also urgently required. Further study is needed to determine the modifiable risk factors for stunting.